Teknologi Pembelajaran dalam Bimbingan dan Konseling: Perkembangan, Implementasi, dan Tantangan Etis di Era Digital - Julham Hukom (CV. SINAR HOWUHOWU, 2026)
The rapid advancement of digital technology has significantly transformed the landscape of guidance and counseling (BK) services, both in school settings and higher education. This article presents a systematic literature review examining the development of learning technology in the field of guidance and counseling in Indonesia and globally, including its implementation forms, benefits, and ethical challenges. Using a library research approach, this study analyzed 15 primary sources published between 2013 and 2025 from accredited national and international journals. The review reveals that the implementation of technology in BK services has evolved from the use of basic ICT tools (email, telephone) to more sophisticated forms such as cybercounseling, e-counseling via videoconferencing platforms, and the integration of Artificial Intelligence (AI)-based chatbots. Evidence suggests that technology-mediated counseling services increase access, eliminate geographical barriers, and can be effective in addressing academic problems, anxiety, and other psychological issues. However, several significant challenges persist, including data privacy and security concerns, the risk of losing humanistic relational elements in the counseling relationship, limited digital literacy among counselors, unequal access to digital infrastructure, and unresolved ethical and professional regulatory issues. This article concludes with recommendations for counselors and institutions to adopt a balanced approach by positioning technology as a complementary tool that supports, rather than replaces the human dimension of counseling services.